Concepts and Treatment Approaches in Nonalcoholic Fatty Liver Disease. (30th November 2014) - Halegoua-De Marzio, Dina L.; Fenkel, Jonathan M.
Abstract : Nonalcoholic fatty liver disease (NAFLD) affects up to 30% of adults and is the most common liver disease in Western nations. NAFLD is associated with central adiposity, insulin resistance, type 2 diabetes mellitus, hyperlipidemia, and cardiovascular disease. It encompasses the entire spectrum of fatty liver diseases from simple steatosis to nonalcoholic steatohepatitis (NASH) with lobular/portal inflammation, hepatocellular necrosis, and fibrosis. Of those who develop NASH, 15–25% will progress to end stage liver disease and hepatocellular carcinoma over 10–20 years. Its pathogenesis is complex, and involves a state of lipid accumulation due to increased uptake of free fatty acids into the liver, impaired fatty acid beta oxidation, and increased incidence of de novo lipogenesis. Plasma aminotransferases and liver ultrasound are helpful in the diagnosis of NAFLD/NASH, but a liver biopsy is often required for definitive diagnosis. Many new plasma biomarkers and imaging techniques are now available that should improve the ability to diagnose NAFLD noninvasively Due to its complexity and extrahepatic complications, treatment of NAFLD requires a multidisciplinary approach with excellent preventative care, management, and treatment. This review will evaluate our current understanding of NAFLD, with a focus on existing therapeutic approaches and potential pharmacological developments.